Reflective Thinking among Teachers: Development and Preliminary Validation of Reflective Thinking for Teachers Questionnaire (Alberta Journal of Educational Research, 2019)
This article describes the development and validation of the 32-item Reflective Thinking for Teachers Questionnaire (RTTQ) designed to assess the process of reflective thinking among teachers. The process of instrument development and validation is described, along with a review of relevant literature related to the process of reflective thinking. An exploratory factor analysis and a subsequent confirmatory factor analysis of the responses of a large sample (N = 659) was carried out. The results of the study showed that the structural equation model developed fitted the questionnaire data well. The confirmatory factor analysis produced goodness of fit indices within an acceptable range, and the questionnaire appeared to be a reliable instrument that would assist in the assessment and improvement of the quality of reflective thinking among teachers.Cet article décrit le développement et la validation du questionnaire à 32 questions portant sur l’évaluation des compétences de la pensée critique chez les enseignants (Reflective Thinking for Teachers Questionnaire). Nous décrivons le processus d’élaboration et de validation du questionnaire, et présentons un examen de la littérature sur la pensée réflexive. Les réponses d’un échantillon de taille importante (N = 659) ont été soumises à une analyse factorielle exploratoire suivie d’une analyse factorielle confirmatoire. Les résultats indiquent que le modèle d’équation structurelle élaboré s’ajuste bien aux données du questionnaire. L’analyse factorielle confirmatoire a produit des valeurs élevées pour la qualité d’ajustement se situant dans une fourchette acceptable, et le questionnaire semble avoir été un outil fiable pour appuyer l’évaluation et l’amélioration de la qualité de la pensée réflexive chez les enseignants.Mots clés : pensée réflexive; formation des enseignants; validation d’instruments; élaboration d’instruments; pensée critique